REPRESENTASI CALON GUBERNUR RIAU TAHUN 2013 DALAM RUBRIK POLITIKADA HARIAN TRIBUN PEKANBARU PEKANBARU - Rahman, Mukmini; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Local elections is a form of democracy that is done by the local government. Theachievement of local elections Riau Province in 2013 was the desire for thepeople of Riau. But it is not immune from the interference of politics driven massmedia as the connection between the political elite of society. Tribun Pekanbaru,as one of the largest media Riau under the Kompas Group known as theindependence slogans, in this case help provide information to the public aboutthe development of Riau governor's election in 2013. This study aims to determinethe representations and social cognition candidate for election news on TribunPekanbaru Riau governor.This study used qualitative methods to the presentation of descriptive analysis.The data analysis technique used is critical discourse analysis proposed by TeunA Van Dijk. The data collection was done by using documentation, interviews andFocus Group Discussion ( FGD ). As for the subject of this study is PekanbaruTribune reporter. While the object is to be the news on the rubric PolitikadaTribune Pekanbaru 1st to July 10th 2013.These results indicate, first, the structure of the text in the discourse as a wholedepicts a representation of the candidate for governor of Riau in 2013 had abalance in reporting. It is found in almost all the elements in the analysis of textstructure. Second, the analysis of social cognition Pekanbaru Tribune reporterconsisting of cognition and cognition readers. Cognition journalists in electionreporting in 2013 shows that the Tribune reporter Pekanbaru provide significantinformation to the public on each candidate, they are Anas Maamun -Arsyadjuliandi Rachman, Herman Abdullah - Agus Widayat, Lukman Edy -Suryadi Khusaini, Achmad - Masrul Kasymi, and Jon Erizal-Mambang Mit. Whileon cognition readers see how readers view the news published by TribunePekanbaru in the preaching of each candidate.Key Word: Representation, Tribun Pekanbaru, Riau Governor, Politikada Rubric,Social Cognition.